0126 A Novel Non-invasive Approach for Measuring Upper Airway Collapsibility in Mice. (12th April 2019) - Nishimura, Yoichi; Arias, Rafael S; Pho, Huy; Pham, Luu Van; Curado, Thomaz Fleury; Polotsky, Vsevolod Y; Schwartz, Alan R
Abstract: Introduction: Invasive procedures were previously developed for measuring pharyngeal collapsibility in rodents during expiration, when declining neuromuscular activity makes the airway unstable. We developed a non-invasive approach for streamlining collapsibility measurements by characterizing responses in physiologic markers of dynamic expiratory airﬂow obstruction to negative nasal pressure challenges. Methods: Anesthetized mice were instrumented to monitor upper airway pressure-ﬂow relationships with head-out plethysmography while nasal pressure was ramped down from ~ +5 to −20cm H2 O over several breaths. Inspiratory and expiratory ﬂow, volume, and timing characteristics were assessed breath-wise. Critical pressure (Pcrit ) was estimated at transitions in expiratory amplitude and timing parameters, and compared to gold standard Pcrit measurements when nasal and tracheal pressures diverged during expiration. Predictions equations were constructed in a development data set (n = 8) and applied prospectively to a validation data set (n = 16) to estimate gold standard Pcrit. Results: The development data demonstrated that abrupt reversals in expiratory duration and tidal volume during nasal pressure ramps predicted gold standard Pcrit measurements. After applying regression equations from the development to a validation dataset, we found that a combination of expiratory amplitude and timing parameters proved to be robust predictors of gold standard Pcrit with minimal bias and narrow conﬁdence intervals. Conclusion: Markers of expiratory airﬂow obstruction can be used to model upper airway collapsibility, and can provide sensitive measures of changes in airway collapsibility in rodents. This approach streamlines repeated non-invasive Pcrit measurements, and facilitates studies examining the impact of genetic, environmental, and pharmacologic factors on upper airway control. Support (If Any): NIH R01HL128970, R01HL133100, R01HL138932, R01HL144859